Influence of green information on environmental awareness: a case study of clothing tags - Hsing-Tzu Chang; Jui-Che Tu; Kai-Cheng Jiang; Tsai-Feng Kao (Discover Sustainability)
Abstract A United Nations report has revealed that 17% to 20% of global industrial wastewater pollution comes from textile dyeing and finishing processes, where toxic substances infiltrate the soil through the water cycle. This positions the fashion industry as the second-largest polluting industry in the world. Currently, due to consumers’ green consumption behaviors are influenced by the source of label information, recognition of eco-labels, and academic literature contains limited research on the design and perspectives of green information integrated into clothing tags. Therefore, based on S–O-R model, this research explored the correlation between consumers’ perception on the green information, how much they are involved in it, and their environmental awareness. The research was conducted by using purposive and snowball sampling. A total of 300 questionnaires were distributed via postal mail and online platforms. After excluding 36 invalid responses, 264 valid questionnaires were retained. The data were analyzed by adopting SPSS 20.0 and AMOS 25. Based on this analysis, the study summarizes the key factors of green information that enhance consumers’ environmental awareness and identifies design elements in green clothing tags that can further promote environmental awareness. According to our research findings, green information has a significant and direct negative influence on consumers' environmental awareness. However, green-designed clothing tags significantly positively influence consumers' environmental awareness. Moreover, when green information is conveyed through green-designed clothing tags, it exerts a significant and indirect positive influence on environmental protection. This demonstrates that the green information displayed on clothing tags enables consumers to easily grasp the environmental message, sparks their interest in environmental protection, and consequently raises their environmental awareness. It is expected that by raising consumers’ environmental awareness, this study can also contribute to can serve as a pre-purchase reminder, effectively promoting environmental protection by significantly reducing unnecessary purchases, accumulation, and eventual disposal by consumers. Accordingly, it will help decrease carbon emissions from clothing production, minimize resource waste, and enhance the quality of the environment, resources, and the health of all living beings, including humans.